(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate the relationship between bone density and clinical and paraclinical factors in patients with cirrhosis. Materials and methods: A cross-sectional descriptive analysis involving 33 patients with cirrhosis at the Department of Internal Medicine - Endocrinology - Musculoskeletal, Hue University of Medicine and Pharmacy Hospital. The study was conducted from April 12, 2024 to November 25, 2024. Bone mineral density was measured by the Medix DR machine in the lumbar spine L1-L4 and the femoral neck of the non-dominant leg. Results: At the femoral neck, 42.4% of patients had osteopenia, and 12.1% had osteoporosis. At the lumbar spine, the rates were 42.4% for osteopenia and 27.3% for osteoporosis. The average bone density mineral for both the femoral neck and lumbar spine was was significantly lower in individuals aged 55 and older compared to those younger than 55 (p < 0.05). The risk of osteopenia or osteoporosis at the lumbar spine and femoral neck was 5.71 times and 5.5 times higher, respectively, for the group aged 55 and older compared to the younger group (p < 0.05). Individuals who consumed alcohol heavily had lower average bone density at both the femoral neck and lumbar spine (p < 0.05). A significant difference was also observed in the average Child-Pugh score and the bone density at the lumbar spine (p = 0.04). Conclusion: Bone mineral density is influenced by various factors, including age, alcohol consumption, and the Child-Pugh score in patients with cirrhosis. It is advisable to increase the study sample size and to routinely assess bone density in this population.